PAI Teacher Social Competence on Student Learning Motivation - Lubis, Melati Br.; Siregar , Nur Khofifah; Marsyela, Marsyela; Pras , Jogi; Nurmaini, Ella; Maulida, Sifa; Siregar , Ahmad Rinaldi (IKAMAS: Manajemen Pendidikan Islam, 2023)
We know that teachers generally refer to professional educators with the main task of educating, teaching, guiding, directing, training, etc. Assess, and evaluate students. We also know that teacher competence is the ability or capacity of a person to do various tasks in a job, where this ability is determined by two factors which are intellectual ability and physical ability. PAI teachers in shaping the character of these students, we can know that PAI plays a role in guiding, directing, giving an example of evaluating, in shaping the character of discipline in students.Although there are still obstacles in the process of fostering these students. Teacher competence has various kinds of competencies, namely: pedagogic competence, personality competence, social competence and professional competence.And there is also what is called social competence, namely a person's ability to communicate and interact verbally and in writing with students, teachers, educators, parents of students Nor the community.